Traffic speed-flow relationships for Singapore roads - Mak, Chin Long. (2009)
Speed-flow relationship and capacity are commonly used in the evaluation of traffic measures. The speed-flow curves provide the basis for measures of effectiveness and level of service for uninterrupted flow facilities. They are also useful in the design, operation and economic appraisal of such facilities. Due to differences in driver behaviour, roadway conditions and traffic flow characteristics between Asian and Western countries, traffic stream models developed overseas may not be applicable to Singapore roads. This study attempts to develop traffic speed-flow relationships for six-lane expressways and arterial roads as well as to derive passenger car equivalents (PCE) for through movement at signalised intersections for Singapore traffic conditions.